Hydrological Analysis of Batu Dam, Malaysia in the Urban Area: Flood and Failure Analysis Preparing for Climate Change - Allias Omar S.M.; Wan Ariffin W.N.H.; Mohd Sidek L.; Basri H.; Moh Khambali M.H.; Ahmed A.N. (MDPI, 2023)
climate change; disaster management; failure analysis; flooding; hydrological cycle; urban area; article; climate change; dam (barrier); failure analysis; flood mitigation; human; Malaysia; precipitation; urban area; flooding; Malaysia; probability; reproducibility; Batu Dam; Malaysia; Selangor; West Malaysia; Climate Change; Floods; Malaysia; Probability; Reproducibility of Results